Harmonization of the Application of Customary Law and Positive Law in Village Communities of Malang Regency - Nany Suryawati; Martika Dini Syaputri (AIBPM Publisher, 2021)
Ngadas Village is a village with an interesting order of life and customs like many other villages. The people have lived long with the customs and norms of local wisdom. Our study aims to investigate the harmonization of both customary law and national law in Ngadas Village. The customary law includes the local wisdom value as a philosophy and obeys positive law. To understand the harmonization, we use an empirical juridical approach in understanding the role of government officials in preserving customs and positive law. Subsequently, we discuss the harmonization through the role of government officials covering aspects of community life. Our findings indicate that the positive law serves as a reference to the customary law. The customary law is in line with national interests and laws and national law. Likewise, the customary law is in harmony with religious elements. This denotes the importance of the village's official roles for the local community's interests.